Tipificação de patologias em revestimentos argamassados - Beatriz Bernardes Dias Ferreira (2010)
The mortar is a product of greater use in construction, being present in the coating and settlement of masonry. Despite the intense use of mortar coating, is very frequent occurrence of pathologies in them, causing damages to several involved sectors. Becomes important, therefore, the study of main incidents pathologies on this type of coating and the release of this information in order to avoid repeating the same mistakes.This work aims to study the major incidents pathologies in mortar coating, emphasizing the influence that the characteristics of materials, the mixing of them, the methods of implementation and the action of external factors, have on the coatings, and the inter relation between these several factors with the durability and performance of mortars. So it was performed a literature review in order to gather information about the subject, also carried out a case study with visits to fifteen buildings. In the surveys sought to identify the main pathologies present in the buildings, checking the rate of occurrence of them and their possible causes. It was concluded that among the identified pathologies in the inspected buildings the ones that showed the highest percentage of occurrence were cracks present in 87% of the buildings, followed by detachments of dustiness with 73% and mold or mildew identified in 47% of the studied cases.